2010
DOI: 10.1038/sc.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical atherosclerosis is related to injury level but not to inflammatory parameters in spinal cord injury subjects

Abstract: Study design: Cross-sectional. Objectives: Individuals with spinal cord injury (SCI) exhibit increased carotid intima-media thickness (IMT) and are reported to be exposed to higher circulating levels of inflammatory mediators. This study evaluated the relationship between inflammatory markers and carotid surrogates of cardiovascular risk in subjects with SCI. Setting: São Paulo, Brazil. Methods: A total of 65 nondiabetic, nonhypertensive, sedentary, nonsmoker men (34 with SCI; 31 healthy subjects) were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 20 publications
(26 reference statements)
0
31
0
2
Order By: Relevance
“…3 Interestingly, this process is not explained by traditional cardiovascular risk factors, indicating that alternative mechanisms might influence the development of early atherosclerosis in such individuals. 3 On the other hand, patients with SCI are exposed to higher circulating levels of inflammatory markers in comparison with able-bodied individuals, 4 suggesting inflammatory mechanisms to be potential candidates to explain the increased cardiovascular risk in these subjects.…”
Section: Introductionmentioning
confidence: 99%
“…3 Interestingly, this process is not explained by traditional cardiovascular risk factors, indicating that alternative mechanisms might influence the development of early atherosclerosis in such individuals. 3 On the other hand, patients with SCI are exposed to higher circulating levels of inflammatory markers in comparison with able-bodied individuals, 4 suggesting inflammatory mechanisms to be potential candidates to explain the increased cardiovascular risk in these subjects.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to results demonstrating no difference in CA-IMT between physically active SCI and age-matched controls. (14) Our absolute CA-IMT measurements for all SCI were slightly larger than those previously reported in 28 wheelchair athletes, ϳ0.10 mm, but were 0.15 mm smaller than those reported for 34 SCI, including injuries causing paraplegia and tetraplegia (18). Interestingly, the normalized IMT in the BA was smaller in our SCI group.…”
Section: Discussionmentioning
confidence: 39%
“…Interestingly, the mortality risk from CVD is 5-10% greater in SCI compared with age-and risk factor-matched able-bodied individuals (22). Specifically, it has been demonstrated that spinal cord injury leads to greater coronary artery calcification (24) and T-wave abnormalities (33), but evidence is equivocal regarding the development of subclinical atherosclerotic markers of carotid artery (CA) intima-media thickening and arterial stiffness (14,18). The potential mechanisms for atherosclerosis in SCI include disorders of carbohydrate metabolism (1), dyslipidemia (1,28), lower-extremity physical inactivity, and the resultant loss of lean body tissue (21), reduced daily energy expenditure (5), and greater prevalence of type 2 diabetes (2).…”
mentioning
confidence: 99%
“…Além do baixo nível de atividade física, coexistem, nesta população, uma miríade de condições deletérias para a saúde como obesidade central com elevada quantidade de gordura visceral, altos índices da proteína C reativa (associada ao estado inflamatório), aumento da espessura íntima da carótida, e o perfil lipídico desfavorável é mais uma condição que predispõe estas pessoas a eventos cardiovasculares [5][6][7][8] .…”
Section: Introductionunclassified